please give the answer for this
Attachments:
![](https://hi-static.z-dn.net/files/d9c/063983ecfdcd5c0eea1e2532c568dcd8.jpg)
Answers
Answered by
0
Answer:
It's true for all........... duh
Answered by
0
Answer:
hope it helps!
please mark as brainliest!!!
thanks!!!
Step-by-step explanation:
x will always be equal to -(-x) because -(-) is + since () represents multiplication. and any negative number multiplied by a negative number is positive.
so,
1. -2/9
-[-(-29)] (because - ( - x ) = x and x is multiplied my -1 twice.)
= -(2/9) (we first remove on of the parenthesis)
= -1 x 2/9 (- x 2/9 = -1 x 2/9)
= -2/9 (the answer!)
so, x which is -2/9 in this case remains the same.
apply the same to the next problem
3. 15/17
-[-(15/17)]
= -[-15/17]
= 15/17 (since -1 x -1 = +1)
apply the same to the next problem
Similar questions